3D modelling and printing of craniofacial implant template. Issue 2 (4th March 2019) - Gill, Deepkamal Kaur; Walia, Kartikeya; Rawat, Aditi; Bajaj, Divya; Gupta, Vipin Kumar; Gupta, Anand; Juneja, Mamta; Tuli, Rakesh; Jindal, Prashant
Abstract : Purpose: To relieve intracranial pressure and save patient inflicted with severe head injury, neurosurgeons restore cranial defects. These defects can be caused because of trauma or diseases (Osteomyelitis of bone) which are treated by cranioplasty, using the preserved bone of patient. In case of non-availability of bone, a cranial implant is generated using a biocompatible synthetic material, but this process is less accurate and time-consuming. Hence, this paper aims to present the use of rapid prototyping technology that allows the development of a more accurate patient-specific template and saves the surgery time. Design/methodology/approach: A five-year-old girl patient having cranial defect was taken up for cranioplasty. CT (computed tomography) scans of the patient were used to generate 3D design of the implant suitable to conceal the defect on the left frontal portion using CAD/CAM (computer-aided design/ computer-aided manufacturing) software. The design was used for 3D printing to manufacture a base template, which was finally used to fabricate the actual implant using Simplex® P bone cement material to conceal the defect. Findings: Surgery using Simplex® P implant was performed successfully on the patient, giving precise natural curvature to left frontal portion of the patient, decreasing surgery time by about 30 per cent. Originality/value: The case demonstrates the development of a convenient, time-saving and aesthetically superior digital procedure to treat cranial defect in the absence of preserved bone flap using CT scan as input. 3D modelling and printing were deployed to produce an accurate template which was used to generate an implant using bone cement biocompatible material.